Analisis Produktivitas dan Efisiensi Mobile Crane dalam Produksi Tiang Pancang: Studi kasus di PT. Adhi Beton Kabupaten Purwakarta - Assyfa Hermalia Puteri; Ananda Edo Pratama; Indra Ginanjar; Defagy Faudril; Moch Paridzi Almauludy; Salva Handika; Rifan Rizky Sabila; Deny Ernawan (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
Heavy equipment effectively plays a key role in ensuring productivity and efficiency in the precast concrete industry of spun pile concrete at PT Adhi Beton Purwakarta. One of the heavy equipment that plays an important role is the mobile crane, especially for moving large concrete components. In this study, field data was processed by analyzing the productivity and efficiency of the Tadano GR-500EXL type mobile crane with a capacity of 50 tons. Current problems are high idle time, lack of operational synchronization, and suboptimal utilization of technological features on the crane unit. The results show that spun pile concrete weighing 6.78 tons based on the analysis of heavy equipment productivity is 40.68 tons/hour with the number of mobile crane heavy equipment needed as many as 2 units, and the efficiency for crane heavy equipment reaches around 68%. The amount of productivity and needs are to support the target of achieving precast concrete production, especially spun pile concrete. Thus, it is expected that the amount of productivity and the number of mobile crane heavy equipment needs are optimal to support production.